UPAYA MENINGKATKAN MOTIVASI SISWA DENGAN METODE OUTDOOR STUDY MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Nur Fatma, Intan; Juwita, Putri; Nazirah Aulia, Fathin; Mayang Sari, Cintya; Nadia; Nauval Khairi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student learning motivation through the application of the outdoor study method in Natural and Social Sciences (IPAS) for fourth-grade elementary school students. The study used a Classroom Action Research (CAR) approach with a two-cycle design, each encompassing planning, implementation, observation, and reflection. The subjects were fourth-grade students at the UPT SD Negeri 060823 Medan. Data collection techniques included observation, interviews, learning achievement tests, and documentation. The results showed that the application of the outdoor study method significantly increased student learning motivation. In the first cycle, student learning motivation was in the moderate category at around 55%, while in the second cycle it increased to around 90%. This increase in motivation was characterized by increased student activeness, enthusiasm in participating in learning, and student involvement in direct observation activities in the school environment. Based on the results, it can be concluded that the outdoor study method is effective as an alternative contextual learning method to increase student learning motivation in IPAS in elementary school.